Analysis Of Registers Used By Tni Soldiers In The Serigala Langit Movie - Rachma Firdaus, Intan; Sholiyah, Sholiyah (LPPM Universitas Duta Bangsa Surakarta, 2023)
The difference in language between one person and another is called variety. Variations in linguistic items include dialect, register and style. The register is various languages that depend on the occasion and social setting. Registers are usually known only to the people who use the words. Register relates to specific occupations and vocabulary. Therefore, this study aims to determine the terms categorized as registers used within the community, the linguistic forms used, and the motives used by army soldiers. This research utilizes a descriptive qualitative approach as it studies sociolinguistics, which deals with investigating linguistic forms (proposed by Morley) and motives (proposed by Hockett) of registers used in conversation. The study reveals that the Air Force army troops in the Serigala Langit Movie categorize several words and compound words as registers. Categorize the words as nouns and verbs for grammatical categories, and let them function as subjects, predicates, and objects in utterances. These registers are based on prestige motives and need fulfilment motives. Therefore, there will always be a motive behind the speakers' registers, depending on the occasion and the social setting